Regulatory-required post-marketing database studies in Japan could be leveraged to assess important potential risks as well as identified risks - Hiroshi Yamazaki; Ko Nakajo; Naoki Hirose; Li Yan; Sun Yeop Lee; Yongjing Zhang; Hong Qiu; Chieko Ishiguro (Frontiers in Pharmacology)
BackgroundTo investigate the characteristics of post-marketing database studies (PMDS) included in risk management plans (RMPs) across all therapeutic areas in Japan.MethodsTwo researchers systematically and independently reviewed all RMPs listed on the Pharmaceuticals and Medical Devices Agency website from April 2013 to December 2023. PMDS contained in RMPs were identified, reviewed, and summarized by study design, target objectives, and data source. Specific objectives were linked to the data source.ResultsAmong 648 RMPs retrieved/reviewed, 85 PMDS were identified from 63 RMPs targeting 138 safety and five effectiveness objectives. Among 85 PMDS, 57 (67.1%) PMDS targeted important identified risk and 29 (34.1%) targeted important potential risk. Cohort studies were the most prevalent study design (74/85, 87.1%), and 74.1% (63/85) included a comparator group. Common target safety objectives included “infections and infestations”, “metabolism and nutrition disorders”, “cardiac disorders” and “vascular disorders”. The Medical Data Vision database was the most frequently used data source for PMDS (32/85, 37.5%) followed by the Medical Information Database Network (MID-NET®) (18/85, 21.2%) and JMDC (9/85, 10.6%)ConclusionIn Japan, PMDS are usually cohort studies with targeted safety objectives. Most studies currently target important identified risk rather than important potential risk and may not make full use of the advantages of PMDS that can include large populations, comparator groups, and that can assess the occurrence of rare adverse events. These results could be informative for pharmaceutical companies planning post-marketing studies as pharmacovigilance activities. Early public availability of PMDS protocols would promote improved study methodology and could potentially improve the scientific value of PMDS in Japan.